Digital Green Banking and the Shift in Environmental Accountability: A FinTech-Accounting Integration (The Journal of Theoretical Accounting Research, 2025)
Financial sector digital transformation has supported the emergence of green banking by combining environmental concerns with sustainability-focused financial operations. Management accounting, more accountable for environmental cost monitoring and performance assessment, offers a critical platform for internal accountability. This study aims to investigate how digital green banking practices enabled by FinTech tools can be integrated into management accounting systems to enhance environmental accountability. A mixed-methods design was used, which integrated quantitative surveys of 200 respondents with qualitative interviews and secondary analysis of data. Findings show that adoption of FinTech enhances the accuracy of environmental costs, reporting timeliness, and budgeting for sustainability, with statistical testing yielding statistically significant associations. Case-based evidence reveals diverse uses across commercial, development, and cooperative banks, with quantifiable gains in accountability and efficiency. Evidence indicates that integrating digital green banking transforms the function of management accounting, promoting it as a key enabler for the integration of sustainability into strategic decision-making.